An agenda for science communication research and practice - James N. Druckman; Kirsten M. Ellenbogen; Dietram A. Scheufele; Itzhak Yanovitzky (Proceedings of the National Academy of Sciences, 2025)
Science should not unilaterally dictate individuals’ decisions or public policies. Yet, it provides a vital source of information for societies and individuals that can often improve outcomes and well-being. This requires, however, the effective communication of scientific information. We identify two paradigms for science communication. One focuses on dissemination, often seeking to inform, reframe, or correct beliefs. Another emphasizes participation and engagement with the goal of improving public understanding of science and scientists’ understanding of the public’s concerns, needs, and values. We argue that participatory approaches better address contemporary challenges concerning scientific uncertainty, politicized science, artificial value neutrality, and a reactive science communication infrastructure. These approaches though need to move away from transactional partnerships toward more cocreation and coproduction of knowledge. They also need to focus more on less motivated and/or engaged populations. Investment in a participatory infrastructure is crucial given that even the most path-breaking science only matters if it can be adequately communicated to relevant stakeholders.